2020
DOI: 10.1108/mij-06-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and its associated factors among medical students of Jazan University, Jazan, Saudi Arabia

Abstract: Purpose The purpose of this study is to assess the prevalence of burnout syndrome and its associated factors among medical students at Jazan University, Jazan, Kingdom of Saudi Arabia. Design/methodology/approach A cross-sectional survey was conducted among 440 randomly selected medical students at Jazan University. The questionnaire used for this study was based on the Copenhagen Burnout Inventory. Findings The overall prevalence of burnout was estimated at 60.2% (95% CI 55.6–64.8). The prevalence was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 32 publications
0
20
1
Order By: Relevance
“…Tables 2 and 3 show that a significant difference in CBI between genders is recorded in studies conducted in different countries [ 29 , 32 , 34 , 37 ], but not in studies among populations from Saudi Arabia and Egypt [ 29 , 31 ]. Also, CBI recognizes a significant difference between the types and subscales of burnout among studies carried out in South Africa and Malaysia [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tables 2 and 3 show that a significant difference in CBI between genders is recorded in studies conducted in different countries [ 29 , 32 , 34 , 37 ], but not in studies among populations from Saudi Arabia and Egypt [ 29 , 31 ]. Also, CBI recognizes a significant difference between the types and subscales of burnout among studies carried out in South Africa and Malaysia [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, MBI is significantly different between genders in published research [ 41 , 44 , 47 , 55 57 ], and was found to be higher among females in studies conducted in countries such as the Netherlands [ 28 , 30 ], USA, Lebanon, and Romania [ 55 , 57 ]. Two studies recorded that males have higher burnout rates than females [ 34 , 47 ], which can be attributed to genetics and socio-economic statuses of those countries. As the educational attainment increases, burnout increases among participants from different countries and populations [ 30 , 34 , 35 , 40 , 54 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Academic burnout is more common among medical students and affects their mental health, academic performance and interpersonal relationships [ 11 , 12 ]. Increasing stress associated with lengthy learning processes and the academic environment, which presents students with many challenges [ 13 ]. Such consequences of emotional burnout can be considered depression and poor psychosomatic state [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%